WORLD OUTLOOK-PARADIGM CONFLICT AS A DETERMINANT OF SOCIAL CRISIS AND AGGRESSIVE YOUTH CONSCIOUSNESS - Andrey N. Zakharin (Вестник Северо-Кавказского федерального университета, 2022)
This article examines the social and philosophical essence of world outlook-paradigmatic conflict as a product of the turbulence in the information field of culture, and its influence on the minds of youth, vyzavayuschee as positive (pre-conflict and post-conflict) as negative (conflict-crisis, aggressive) states of consciousness.